2007
DOI: 10.1098/rspb.2007.1511
|View full text |Cite
|
Sign up to set email alerts
|

The trade-off between number and size of offspring in humans and other primates

Abstract: Life-history theory posits a fundamental trade-off between number and size of offspring that structures the variability in parental investment across and within species. We investigate this 'quantity-quality' trade-off across primates and present evidence that a similar trade-off is also found across natural-fertility human societies. Restating the classic Smith-Fretwell model in terms of allometric scaling of resource supply and offspring investment predicts an inverse scaling relation between birth rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
90
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 36 publications
4
90
0
Order By: Relevance
“…The quality-quantity trade-off has been empirically demonstrated in species that produce litters or clutches, where large litter size often leads to small offspring size, slow growth rates, and reduced survival, particularly under conditions of ecological stress (8)(9)(10)(11). Comparative analyses also support a negative interspecific relationship between reproductive rate and offspring size (12,13). The quality-quantity trade-off has rarely been examined in species for which single births are the norm, and for which reproductive rate is determined by the interval between successive births.…”
mentioning
confidence: 70%
“…The quality-quantity trade-off has been empirically demonstrated in species that produce litters or clutches, where large litter size often leads to small offspring size, slow growth rates, and reduced survival, particularly under conditions of ecological stress (8)(9)(10)(11). Comparative analyses also support a negative interspecific relationship between reproductive rate and offspring size (12,13). The quality-quantity trade-off has rarely been examined in species for which single births are the norm, and for which reproductive rate is determined by the interval between successive births.…”
mentioning
confidence: 70%
“…We already know, for example, that humans are subject to the same basic trade-off between offspring size and number as other mammals (Walker et al 2008). Hawkes et al (1998) found that humans fit the predicted value for the product of adult mortality rate and age at maturity, but differed in the product of birth rate and age at maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Population models assume that parents make investment decisions that maximize reproductive success in the face of limited resources [1]. In other words, when certain constraints are met such as energy, effort or time invested in the provisioning of offspring, then it is difficult to invest in the production of additional offspring [2].…”
Section: Introductionmentioning
confidence: 99%